Breakthrough Business Analysis : Implementing and Sustaining a Value-Based Practice. - Hass, Kathleen B. (Berrett-Koehler Publishers, Incorporated, 2014)
Traditional business analysis jobs are going away and are not coming back. BA tools are growing up, and typical BA tasks are being automated and commoditized. Instead of being regarded as documenters, BAs are being sought out to focus on strategy, innovation, and leadership. Breakthrough Business Analysis: Implementing and Sustaining a Value-Based Practiceprovides a framework for implementing a BA practice that is strategically positioned and value-based. Realizing the positive impacts of a value-based BA practice could very well mean the difference between success and failure for businesses negotiating 21st century challenges. Value-based business analysis centers on strategy execution, world-class enterprise capabilities, and delivery of innovative products and services. The framework for implementing and sustaining a value-based BA practice involves three phases: 1. Readiness: "Is our organization ready'" 2. Implementation: "How do we build the BA practice'" 3. Sustainability: "How do we institutionalize and continue to improve BA practices'" Take the lead and be your organization's champion of a value-based, breakthrough BA practice that is focused on value to the customer and wealth to the bottom line.